ATP10A deficiency results in male-specific infertility in mice - Norris, Adriana C.; Yazlovitskaya, Eugenia M.; Yang, Tzushan Sharon; Mansueto, Alex; Stafford, John M.; Graham, Todd R. (Frontiers in Cell and Developmental Biology, 2024)
Over 8% of couples worldwide are affected by infertility and nearly half of these cases are due to male-specific issues where the underlying cause is often unknown. Therefore, discovery of new genetic factors contributing to male-specific infertility in model organisms can enhance our understanding of the etiology of this disorder. Here we show that murine ATP10A, a phospholipid flippase, is highly expressed in male reproductive organs, specifically the testes and vas deferens. Therefore, we tested the influence of ATP10A on reproduction by examining fertility of Atp10A knockout mice. Our findings reveal that Atp10A deficiency leads to male-specific infertility, but does not perturb fertility in the females. The Atp10A deficient male mice exhibit smaller testes, reduced sperm count (oligozoospermia) and lower sperm motility (asthenozoospermia). Additionally, Atp10A deficient mice display testes and vas deferens histopathological abnormalities, as well as altered total and relative amounts of hormones associated with the hypothalamic-pituitary-gonadal axis. Surprisingly, circulating testosterone is elevated 2-fold in the Atp10A knockout mice while luteinizing hormone, follicle stimulating hormone, and inhibin B levels were not significantly different from WT littermates. The knockout mice also exhibit elevated levels of gonadotropin receptors and alterations to ERK, p38 MAPK, Akt, and cPLA2-dependent signaling in the testes. Atp10A was knocked out in the C57BL/6J background, which also carries an inactivating nonsense mutation in the closely related lipid flippase, Atp10D. We have corrected the Atp10D nonsense mutation using CRISPR/Cas9 and determined that loss of Atp10A alone is sufficient to cause infertility in male mice. Collectively, these findings highlight the critical role of ATP10A in male fertility in mice and provide valuable insights into the underlying molecular mechanisms.